Antidepressant medication dispensing among montelukast initiators. (November 2013) - Zhou, Esther H.; Kaplan, Sigal; Mosholder, Andrew; Moeny, David; Ding, Yulan; Wu, Yute; Iyasu, Solomon; Hammad, Tarek A.
Abstract Objective: This study investigates the potential association between montelukast use and psychiatric adverse events by monitoring changes in antidepressant medication dispensing rates before and after initiating montelukast. Methods: The primary study group of montelukast initiators was identified using the Wolters Kluwer's SOURCE Lx® pharmacy claims database (WK). This group included 232 159 patients ≤45 years old who had at least two montelukast prescriptions from 2003 to 2007. Comparison groups comprised of 264 704 fluticasone initiators and 89 635 long-acting β-agonist corticosteroid (LABA/ICS) initiators were also identified. Antidepressant medication dispensing rates in these three groups were determined using WK, and changes in rates before and after the first asthma controller medication prescription date were evaluated using interrupted time-series analysis (ITS). ITS was performed separately for four age categories, with a focus on youth (12–17 years) and young adult (18–24 years). Results: For patients 18–24 years old, antidepressant medication dispensing rates increased significantly after initiating montelukast [1.93% (1.55–2.32%, p < 0.001)] but also after initiating fluticasone and LABA/ICS [1.72% (1.30–2.15%, p < 0.001) and 2.76% (2.35–3.17%, p < 0.001)]. Similar patterns were observed across the three medication groups for other age categories but these differences were not all significant. Conclusions: Small increases in antidepressant medication dispensing rates occurred after initiating montelukast. However, similar increases were observed in the fluticasone and LABA/ICS comparison groups. The results of this study cannot support a specific association between initiation of montelukast treatment and an increase in psychiatric adverse effects.